Metastatic Neoplasms to the Vulva—A Review. Issue 2 (8th April 2022) - Heller, Alexis; Breitner, Daniel; Cracchiolo, Bernadette; Heller, Debra S.
Abstract : Introduction: Metastatic neoplasms to the vulva are rare and can pose a diagnostic dilemma. As identification of the primary site can influence patient treatment and prognosis, correct diagnosis is important. Methods: PubMed was searched for applicable publications using the terms vulva, vulvar neoplasms, metastasis, and vulvar metastasis. Results: Most neoplasms metastatic to the vulva originate from other genital sources; however, extragenital primary neoplasms can also metastasize to the vulva. Vulvar metastases often occur in the setting of widespread disease. Conclusions: It is important to consider biopsy for appropriate histologic and immunohistochemical studies, as well as consider patient history to establish the primary site of metastatic lesions to the vulva, allowing optimal therapy.